Correlation of Financial Management with MSME Performance: A Systematic Review of Literature - Amelia Sugangga; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2023)
In the midst of global economic turmoil, Micro, Small and Medium Enterprises MSMEs in Indonesia play an important role as the backbone of the local economy. MSMEs face serious challenges that affect the performance of MSMEs. The novelty of this research lies in the approach of a combination of systematic literature review and in-depth empirical research. Involving stakeholders, especially MSME owners and financial management practitioners, provides valuable practical perspectives. This research has important implications for government policy, related institutions, business practitioners, and academia. The findings are expected to be a strategic guide for the development of training programs, more effective financial management models, and policies that support MSME growth. The method used in this study is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the need for more in-depth regarding the relationship between financial management and MSME performance can provide policy guidance for the government and related institutions, as well as practical insights for MSME owners, business practitioners, consultants, and academics in developing financial management models that are more effective and relevant in the context of MSMEs in Indonesia. This research covers important aspects and makes a substantial contribution in the understanding of the relationship between financial management and MSME performance.